Challenges in breastfeeding consultation among child health service nurses in Sweden: a qualitative study - Ny, Pernilla; Andersson, Johanna; Bergholtz, Elin; Janlöv, Ann-Christin; Ekstrand Ragnar, Maria (Frontiers in Pediatrics, 2025)
BackgroundIn Sweden, evidence-based breastfeeding support is provided as part of the 2022–2027 Swedish Food Agency's breastfeeding strategy. Despite 98% of mothers intending to breastfeed, exclusive breastfeeding rates have dropped from 82% in 2014 to 67% in 2022. Child health service nurses offer guidance regarding breastfeeding to women and their partners. The aim of this study was to explore the challenges perceived by nurses in child health services in providing breastfeeding support to mothers in Sweden.Materials and methodsQualitative methodology, using semi-structured interviews with 12 purposively recruited Child Health Service Nurses (CHSN) in southern Sweden. The interviews were recorded, transcribed verbatim and analysed using qualitative content analysis.ResultsThe analysis identified three main categories, eleven sub-categories and one overall theme: “Taking a step back when balancing breastfeeding communication in a diverse care chain”, which illustrates the CHSNs' struggles during consultations. It reflects communication barriers (i.e., language gaps), relational concerns (i.e., fear of harming trust), cultural factors (i.e., different perceptions of breastfeeding), and organizational hurdles (i.e., time constraints, limited access), prompting CHSNs to delicately balance support while respecting individual choices, often resulting in stepping back from evidence-based breastfeeding advice when faced with obstacles.ConclusionThe study highlights challenges in breastfeeding support among CHSNs, underscoring the need for evidence-based, person-centred care. Further education and guidance are essential to improve support and advance global health goals.